Green energy application technology of litchi pericarp-derived carbon material with high performance. (1st March 2021) - Zhu, Ziyi; Zeng, Xiaoyuan; Wu, Hao; Wang, Yunxiao; Cheng, Hongyu; Dong, Peng; Li, Xue; Zhang, Yingjie; Liu, Huakun
Abstract: To develop a carbon material derived from a green biomass source, this study investigated the production of a derivatized carbon material made from an industrial byproduct, litchi pericarp, through a hydrothermal reaction combined with a high-temperature heat treatment process, and its application in a new energy field was evaluated. Gratifyingly, in the field of sodium ion batteries, the material showed excellent electrochemical performance when evaluated as an anode: the material exhibited a high initial reversible capacity (336.4 mAh/g), an excellent retention rate (98.6%) after 120 cycles and good rate performance (183.2 mAh/g at 500 mA/g). The energy storage mechanism in the material was also determined. Moreover, for a fuel in direct carbon solid oxide fuel cells, the maximum power density was 239 mW/cm 2 at 850 °C. When operating at a constant current density of 250 mA/cm 2, the cell also displayed a stable discharging voltage and platform, and the fuel utilization rate was 66%. As a promising green carbon material with high electrochemical performance, the developed litchi pericarp-derived carbon material shows great potential in the new energy industry. Graphical abstract: Image 1 Highlights: Litchi pericarp-derived carbon can be used in a wide range of clean energy fields. The material can show excellent electrochemical performance in different systems. The sodium storage mechanism was analyzed by different characterization methods.